(untitled) (Scientia Agricola, 2018)
Multiple pathogens affect sugarcane, among them Puccinia melanocephala, the causal agent of brown rust. This disease was first reported in Cuba in 1979 when it was responsible for a severe attack on the main sugarcane variety B4362. The aims of the present study were to give an overview of sugarcane brown rust in Cuba and show the current disease situation in the country. A retrospective analysis regard to sugarcane cultivar composition resistant to brown rust in Cuba was carried out. In addition 154 genotypes, including the most used progenitors in the breeding program and commercial varieties were evaluated under natural infection conditions. The identity of P. melanocephala was verified by Polymerase Chain Reaction (PCR) and by sequencing the ITS1 region. After the introduction of P. melanocephala into Cuba, the susceptible variety, B4362, was replaced by Ja60-5 which remained resistant until 1998. Since 2002, a varietal policy supported by a governmental resolution establishing that any single cultivar cannot occupy more than 20 % of the production area for each production company, local area and province, has been applied. Out of the genotypes evaluated, 49 showed resistance to the disease and 35 intermediate behavior, while 39 were susceptible and 31, highly susceptible. P. melanocephala was detected by PCR in all symptomatic samples and its identify confirmed by sequencing the ITS1 region. The adopted measurement together with permanent phytosanitary monitoring and commercial release of resistant or intermediate cultivars succeeded in avoiding any new epidemic. Inoculum pressure was reduced, even on susceptible and highly susceptible varieties since, by resolution, they cannot occupy more than 10 % of the planted area.